-2
-1
−12
1
Correct answer is D
x2+x−22x2+x−3
= x2+2x−x−22x2+3x−2x−3
= x(x+2)−1(x+2)x(2x+3)−1(2x+3)
= (x−1)(x+2)(x−1)(2x+3)
= x+22x+3
At x = -1,
= −1+22(−1)+3
= 11
= 1
What is the general term of the sequence 3, 8, 13, 18, ...? ...
Simplify the expression a2b4−b2a4ab(a+b)...
Find the value of (0.006)3 + (0.004)3 in standard form...
If a binary operation * is defined by x * y = x + 2y, find 2 * (3 * 4)...
Find the nth term of the sequence 3, 6, 10, 15, 21........
Which of the following is not a measure of dispersion? ...
The value of (0.03)3 - (0.02)3 is ...
In the figure, PQR is a straight line. Find the values of x and y ...